Experimental and analytical study on an air-cooled single effect LiBr-H2O absorption chiller driven by evacuated glass tube solar collector for cooling application in residential buildings. (15th July 2017) - Chen, J.F.; Dai, Y.J.; Wang, R.Z.
Highlights: An air-cooled single effect absorption chiller was designed and fabricated. The performance was tested under a broad range of steady-state conditions. A residential solar air conditioning system using this chiller was analyzed. The solar air conditioning system meets 65% of cooling load with a SCOP of 0.28. Abstract: Solar cooling turns out to be a feasible method to reduce the electricity consumption of air conditioning systems in buildings. Air-cooled single effect LiBr-H2 O absorption chiller has shown advantages in residential applications. It can be driven by common evacuated tube solar collectors, and save water, maintenance expense and space, due to the absence of cooling tower. However, there is no available small capacity commercial air-cooled LiBr-H2 O absorption chiller yet, because of the crystallization risk under ambient conditions. In this work, an air-cooled single effect absorption chiller for which the cooling capacity is 6 kW and a solar air conditioning system were developed. The air-cooled single effect absorption chiller was fabricated and tested under a broad range of steady-state conditions. The chiller was proved successful for real application without crystallization risk and the influence of different operating conditions was also analyzed. Moreover, the performance of a solar air conditioning system using the proposed chiller was investigated for residential cooling application. The results show that the studied absorption chiller can meet about 65% of the total cooling load of the building with an average COPth of about 0.61. Furthermore, 28% of the titled solar radiation is converted into cooling capacity by the solar air conditioning system.